2014
DOI: 10.1002/jbt.21556
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Glucose-6-Phosphate Dehydrogenase and 6-Phosphogluconate Dehydrogenase in Oxidative Stress Induced by Long-Term Iron Toxicity in Rat Liver

Abstract: Reactive oxygen species (ROS) are highly reactive and oxygen-containing molecules that are derived by metabolic activities or from environmental sources. Toxicity of heavy metals including iron has the ability to generate ROS in all living organisms. The pentose phosphate pathway enzymes, which are glucose 6-phosphate dehydrogenase and 6-phosphogluconate dehydrogenase, produce nicotinamide adenine dinucleotide phosphate (NADPH) that enables cells to counterbalance the oxidative stress via the action of the glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 46 publications
3
14
1
Order By: Relevance
“…In both patient groups, results are consistent with the presence of oxidative stress, a characteristic response to metal products (particularly metal ions) released from metal wear and corrosion . Nevertheless, the absolute specificity and sensitivity for the pseudotumor group of 6‐phosphogluconate dehydrogenase, an enzyme that plays a major protective role against oxidative stress, suggest the presence of greater oxidative stress, which, as proposed by Scharf et al, might explain necrosis and the formation of pseudotumors. 6‐Phosphogluconate dehydrogenase, a rate‐limiting enzyme of the pentose phosphate pathway, catalyzes the reduction of NADP to NADPH and is therefore critical in counterbalancing oxidative stress via the glutathione system .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In both patient groups, results are consistent with the presence of oxidative stress, a characteristic response to metal products (particularly metal ions) released from metal wear and corrosion . Nevertheless, the absolute specificity and sensitivity for the pseudotumor group of 6‐phosphogluconate dehydrogenase, an enzyme that plays a major protective role against oxidative stress, suggest the presence of greater oxidative stress, which, as proposed by Scharf et al, might explain necrosis and the formation of pseudotumors. 6‐Phosphogluconate dehydrogenase, a rate‐limiting enzyme of the pentose phosphate pathway, catalyzes the reduction of NADP to NADPH and is therefore critical in counterbalancing oxidative stress via the glutathione system .…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, the absolute specificity and sensitivity for the pseudotumor group of 6‐phosphogluconate dehydrogenase, an enzyme that plays a major protective role against oxidative stress, suggest the presence of greater oxidative stress, which, as proposed by Scharf et al, might explain necrosis and the formation of pseudotumors. 6‐Phosphogluconate dehydrogenase, a rate‐limiting enzyme of the pentose phosphate pathway, catalyzes the reduction of NADP to NADPH and is therefore critical in counterbalancing oxidative stress via the glutathione system . Toxic levels of iron, which increase oxidative stress, were recently shown to upregulate the expression of this enzyme .…”
Section: Discussionmentioning
confidence: 98%
“…The study by Jayasekara et al found 20% of the CKDu cases to have some severity of G6PD deficiency whereas only 2% of the healthy controls had the deficiency [13]. This enzyme is the first rate-limiting enzyme in the pentose phosphate pathway and is responsible for the production of NADPH which is needed in the glutathione reduction process [28]. However, the differential expressions seen in our study groups were not statistically significant on the one-way ANOVA.…”
Section: Discussioncontrasting
confidence: 56%
“…Furthermore, several studies described significant roles of G6PD during abiotic and biotic stress in higher plants [10][11][12]. At the molecular level, G6PD has been well studied in many eutherian species including human, mouse, rats and plants [4,[12][13][14][15][16]. The domesticated one-humped Arabian camel, C. dromedarius, is one of the most important animals in the Arabian Peninsula.…”
Section: Introductionmentioning
confidence: 99%